DEMONSTRASI INOVASI GUMMY CANDIES EKSTRAK TEMULAWAK DAN JAHE SEBAGAI CAMILAN FUNGSIONAL IMUNOMODULATOR DI NAGARI SIPINANG PALEMBAYAN KABUPATEN AGAM - Syofyan; Armenia; Dillasamola, Dwisari; Rachmaini, Fitri; Syakira, Azya Hana; Anjeli, Rada; Aditio, Aditio (Jurnal Hilirisasi IPTEKS, 2025)
This activity aims to introduce innovations in functional snacks based on local herbs and to enhance the knowledge and skills of the community in processing family medicinal plants, particularly temulawak (Curcuma xanthorrhiza) and ginger (Zingiber officinale), into healthy, practical, and economically valuable gummy products. The background of this activity lies in the increasing public demand for functional foods in the post-Covid-19 era, alongside the low interest in consuming herbs in traditional forms, which are often considered bitter and impractical. The methods applied included preparation (site survey, permits, and equipment), educational sessions on the importance of natural immunomodulators, and direct demonstrations of making herbal gummy candies involving the community of Nagari Sipinang, Palembayan District, Agam Regency. Evaluation was conducted through pre-tests and post-tests using questionnaires to measure participants’ improvement in understanding. The results showed a significant increase in community health literacy, from 40% to 85% of participants who understood the benefits and techniques of making herbal gummies. Enthusiasm was evident through active participation in mixing ingredients to molding, with some participants even expressing interest in reproducing the gummies at home. In addition to health benefits, this activity also opened opportunities for local herbal-based businesses, supported by abundant raw materials and simple production processes. In conclusion, the demonstration of making temulawak and ginger gummies was effective in improving community knowledge and skills, while simultaneously encouraging the development of MSMEs based on functional foods. Going forward, continuous mentoring, provision of simple equipment.